Rancang Bangun Cooler Box Portable Menggunakan Peltier - Renita Comalasari Dewi Simanjuntak; Diana Alia; Henna Nurdiansari; Elly Kusumawati (Pusat Riset dan Inovasi Nasional, 2024)
Technological developments and modern industrial needs increasingly demand high energy efficiency in refrigeration machine operations. In this context, the development of a more efficient cooling machine control system is very necessary. Portable cooler boxes using Thermoelectric Cooler (TEC) technology are an innovation to improve the quality and durability of fish caught by fishermen in Surabaya. This research aims to design and test a cooler box that can maintain low temperatures for a long time. This research method uses experimental methods, a series of tools and uses two test plans, namely: static and dynamic testing. The components used are three Peltier elements supported by a 12V 54A power supply, a 10K NTC temperature sensor, and a passive thermal regulator heatsink with fan. Precision testing data on the comparison sensor (thermodigital), obtained an average value of 3.75%. The error value is still categorized as a safe difference value and the tool works according to its function. Test data shows that the Cooler box can maintain a temperature between 5°C to 10°C, this temperature is ideal for slowing down the process of fish spoilage. Testing was carried out by integrating an Arduino Nano for real-time temperature monitoring which is displayed on the LCD and stored on a MicroSD. Test results show that this cooling system is effective in maintaining a stable temperature under various conditions of use, with an electrical energy consumption of 3111.38Wh per 6 hours.